Effect of Pulsed Electron Beam Treatment on the Release Profile of Chloramphenicol from Polylactic Acid–Based Polymeric Scaffolds; High Energy Chemistry; Vol. 57, iss. 3 - Volokhova A. A. Apollinariya Aleksandrovna; Ponomarev D. V. Denis Vladimirovich; Kurzina I. A. Irina Aleksandrovna; Tverdokhlebov S. I. Sergei Ivanovich (2023, 2023)
Title screen